Association of Haemostatic and Inflammatory Biomarkers with Nephropathy in Type 1 Diabetes Mellitus - Caroline Pereira Domingueti; Rodrigo Bastos Fóscolo; Janice Sepúlveda Reis; Fernanda Magalhães Freire Campos; Luci Maria S. Dusse; Maria das Graças Carvalho; Karina Braga Gomes; Ana Paula Fernandes (Journal of Diabetes Research)
This study aimed at investigating the association between haemostatic biomarkers, proinflammatory, and anti-inflammatory cytokines with chronic kidney disease in type 1 diabetic patients. Patients were divided into two groups: with nephropathy (albuminuria ≥ 30 mg/g and/or GFR < 60 mL/min/1.73 m2), n=65; and without nephropathy (albuminuria < 30 mg/g and GFR ≥ 60 mL/min/1.73 m2), n=60. INF-γ, IL-6, IL-10, and TNF-α plasma levels were determined by flow cytometry. VWF, ADAMTS13 antigen, and D-Dimer plasma levels were determined by enzyme-linked immunosorbent assay and ADAMTS13 activity was assessed by fluorescence resonance energy transfer assay. Elevated levels of INF-γ, VWF, ADAMTS13 antigen, D-Dimer, and reduced ADAMTS13 activity/antigen ratio were observed in patients with nephropathy as compared to those without nephropathy (P=0.001, P<0.001, P<0.001, P<0.001, and P<0.001, resp.). Cytokines and haemostatic biomarkers remained associated with nephropathy after adjustments (use of statin, acetylsalicylic acid, angiotensin converting enzyme inhibitor, and angiotensin antagonist). INF-γ, TNF-α, and IL-10 significantly correlated with haemostatic biomarkers. Inflammatory and hypercoagulability status are associated with nephropathy in type 1 diabetes mellitus and an interrelationship between them may play an important role in pathogenesis of diabetic nephropathy.